Commodifying Faith: Symbolic Economies in Media Constructions of the Cikande Halal Industrial Zone - Ahmad, Ikhsan; Turmudi, Hamzah; Muhtadi, Asep Saeful; Mukarom, Zaenal (Jurnal Iman dan Spiritualitas, 2026)
This study investigates how government media construct the Halal Industrial Estate of Cikande (KIHC) as a religious-economic space through the commodification of sacred values. Drawing on key concepts such as religious commodification, Bourdieu’s symbolic capital, and the global halal economy, this research employs a qualitative design using Critical Discourse Analysis integrated with symbolic economy theory. The dataset consists of official press releases, social media posts and promotional materials issued by the Banten Provincial Government between 2019 and 2024. The findings reveal three major mechanisms: the resignification of religious symbols into commercial branding tools, the conversion of religious symbolic capital into economic capital, and the production of futuristic narratives that position KIHC as a center of moral-economic authority. The main methodological challenge arises from the exclusive reliance on government-produced discourse, which limits the study’s ability to capture public reception or contestation. Practically, the study recommends the development of ethical standards for public communication to prevent the reduction of religion into mere commercial branding. This research contributes to the study of religion and media by elucidating how the state deploys religious values as symbolic commodities within Indonesia’s halal industrial development. This article extends theoretical discussions on symbolic economy within the halal industry and offers a conceptual framework for understanding the interplay between religion, state authority, and capitalism in media discourse.